Living Procedural Law in the Constitutional Court: Tension Between Written Norms and Courtroom Practices - M Rizqy Yudha Hariansyah; Innalinsa; Mark Tushnet; Izomiddin (ELQONUN: HUKUM KETATANEGARAAN ISLAM, 2026)
The Constitutional Court, as the guardian of the constitution, adjudicates various types of cases, including disputes over the authority of state institutions and judicial review. In practice, its procedural law has developed not only from statutory provisions and Constitutional Court Regulations, but also from courtroom practices that generate new procedural norms. This phenomenon creates a tension between formally codified procedural law and practice-based norms, referred to as living procedural law, reflecting the view that law evolves through institutional practice and judicial behavior. This study aims to examine the legitimacy of courtroom practices as a source of procedural law and to analyze their implications for legal certainty and consistency in constitutional adjudication. The research employs a normative juridical method with a comparative and case-based approach, comparing types of cases (PUU and SKLN) and periods of decisions. Cases are selected purposively based on procedural innovation or deviation from written norms. The results show that living procedural law emerges through judicially developed filing deadlines, admissibility standards, expanded electronic procedures, and flexible interpretations of legal standing. These practices lead to inconsistencies in procedural application, affecting predictability and legal certainty. This study concludes that a controlled hybrid approach, combining selective codification with limited judicial flexibility, is necessary to balance adaptability, consistency, and procedural legitimacy.